Comparison of the cardiopulmonary effects and recovery characteristics of anesthesia maintenance with xylazine, ketamine and propofol or isoflurane in alpacas (Vicugna pacos) for imaging procedures. (August 2020) - Fujiyama, Masako; Jones, Teela; Ambros, Barbara; Lewis, Kerrie A.; Carrasco, Rodrigo A.; Duke-Novakovski, Tanya
Highlights: Injectable anesthesia might be necessary for long imaging procedures Xylazine, ketamine and propofol combination was evaluated in alpacas The combination compares favorably to using isoflurane anesthesia Oxygen supplementation is recommended when using this combination